Structural Immunology of Complement Receptors 3 and 4 - Vorup-Jensen, Thomas; Jensen, Rasmus Kjeldsen (Frontiers in Immunology, 2018)
Complement receptors (CR) 3 and 4 belong to the family of beta-2 (CD18) integrins. CR3 and CR4 are often co-expressed in the myeloid subsets of leukocytes, but they are also found in NK cells and activated T and B lymphocytes. The heterodimeric ectodomain undergo considerable conformational change in order to switch the receptor from a structurally bent, ligand-binding in-active state into an extended, ligand-binding active state. CR3 binds the C3d fragment of C3 in a way permitting CR2 also to bind concomitantly. This enables a hand-over of complement-opsonized antigens from the cell surface of CR3-expressing macrophages to the CR2-expressing B lymphocytes, in consequence acting as an antigen presentation mechanism. As a more enigmatic part of their functions, both CR3 and CR4 bind several structurally unrelated proteins, engineered peptides, and glycosaminoglycans. No consensus motif in the proteinaceous ligands has been established. Yet, the experimental evidence clearly suggest that the ligands are primarily, if not entirely, recognized by a single site within the receptors, namely the metal-ion dependent adhesion site (MIDAS). Comparison of some recent identified ligands points to CR3 as inclined to bind positively charged species, while CR4, by contrast, binds strongly negative-charged species, in both cases with the critical involvement of deprotonated, acidic groups as ligands for the Mg2+ ion in the MIDAS. These properties place CR3 and CR4 firmly within the realm of modern molecular medicine in several way. The expression of CR3 and CR4 in NK cells was recently demonstrated to enable complement-dependent cell cytotoxicity toward antibody-coated cancer cells as part of biological therapy, constituting a significant part of the efficacy of such treatment. With the flexible principles of ligand recognition, it is also possible to propose a response of CR3 and CR4 to existing medicines thereby opening a possibility of drug repurposing to influence the function of these receptors. Here, from advances in the structural and cellular immunology of CR3 and CR4, we review insights on their biochemistry and functions in the immune system.